Infrastructure 2 Pedestrian System to Increase Human Life and Health Safety - Krzysztof MASLANKA; Pawel SKOKOWSKI (Communications of International Proceedings, 2020)
This paper presents an Infrastructure to Pedestrian (I2P) system to increase human life and health safety. After introducing the reader to the subject of the issue, the authors motivate their research area to increase pedestrian safety on the roads. Then, the concept of the proposed method is presented. Next technical solutions for the prepared I2P system are defined and explained. Moreover, an estimation of the potential profits from the implementation of the proposed concept is shown. The article summarizes brief conclusions.
Keywords: pedestrian safety; infrastructure to pedestrian; accidents; localization.